“POOLING AND SHARING” OR “INTELLIGENT DEFENCE” IN THE FIELD OF SECURITY - Ivaylo ANGELOV (Scientific Journal of Silesian University of Technology. Series Transport)
The European Union is focusing on military capabilities and the fight against terrorism, but to a lesser extent on employment opportunities for immigrant integration, human rights and peace-building and the sustainability of countries and societies in Europe and around it. The European Union has always been proud of its soft power and will continue to do so in the area of security and defence. On the other hand, the idea of Europe as an extremely “civilian power” does not correspond to the changing reality. In this regard, the EU will need to deepen its transatlantic relationship and its partnership with NATO.